2023
DOI: 10.36660/abc.20220701
|View full text |Cite
|
Sign up to set email alerts
|

Implante Valvar Transcateter em Pacientes com Estenose Valvar Aórtica: Uma Overview de Revisões Sistemáticas e Metanálise Incluindo Múltiplas Populações

Abstract: Resumo Fundamento Ensaios clínicos randomizados (ECRs) e estudos observacionais compararam a eficácia e a segurança do implante valvar transcateter (TAVR) e da substituição cirúrgica da valva aórtica (SAVR) em pacientes com estenose aórtica grave. Objetivos Comparar TAVR e SAVR em pacientes com diferentes riscos cirúrgicos, características da população e diferentes válvulas protéticas transcateter. Métodos Uma overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 25 publications
(77 reference statements)
0
8
0
5
Order By: Relevance
“…13 When reanalyzing these data in a meta-analysis, they observed better outcomes in the low-surgical-risk population, for whom conventional surgery is still considered the first treatment option. [10][11][12] The data analysis by Diegoli et al 13 raises questions about the future of treatment for aortic stenosis: will TAVI soon be the preferred strategy for all patients? 13 The key to this answer rests on three main points: the durability of percutaneous prostheses compared to surgical prostheses, the presence of paraprosthetic leaks (still more frequent in TAVI than in surgical prostheses), and the need for pacemaker implantation, also more frequent in TAVI, as also demonstrated by Diegoli et al, 13 especially for selfexpanding prostheses.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…13 When reanalyzing these data in a meta-analysis, they observed better outcomes in the low-surgical-risk population, for whom conventional surgery is still considered the first treatment option. [10][11][12] The data analysis by Diegoli et al 13 raises questions about the future of treatment for aortic stenosis: will TAVI soon be the preferred strategy for all patients? 13 The key to this answer rests on three main points: the durability of percutaneous prostheses compared to surgical prostheses, the presence of paraprosthetic leaks (still more frequent in TAVI than in surgical prostheses), and the need for pacemaker implantation, also more frequent in TAVI, as also demonstrated by Diegoli et al, 13 especially for selfexpanding prostheses.…”
mentioning
confidence: 99%
“…[10][11][12] The data analysis by Diegoli et al 13 raises questions about the future of treatment for aortic stenosis: will TAVI soon be the preferred strategy for all patients? 13 The key to this answer rests on three main points: the durability of percutaneous prostheses compared to surgical prostheses, the presence of paraprosthetic leaks (still more frequent in TAVI than in surgical prostheses), and the need for pacemaker implantation, also more frequent in TAVI, as also demonstrated by Diegoli et al, 13 especially for selfexpanding prostheses. 14 Regarding the first point, preliminary studies have shown similar outcomes in terms of structural degeneration, both for DOI: https://doi.org/10.36660/abc.20230401…”
mentioning
confidence: 99%
See 3 more Smart Citations